2014
DOI: 10.1159/000363212
|View full text |Cite
|
Sign up to set email alerts
|

Benefit of a Contralateral Routing of Signal Device for Unilateral Cochlear Implant Users

Abstract: Objective: To investigate objective and subjective effects of an adjunctive contralateral routing of signal (CROS) device at the untreated ear in patients with a unilateral cochlear implant (CI). Design: Prospective study of 10 adult experienced unilateral CI users with bilateral severe-to-profound hearing loss. Speech in noise reception (SNR) and sound localization were measured with and without the additional CROS device. SNR was measured by applying speech signals at the untreated/CROS side while noise sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 27 publications
3
17
0
Order By: Relevance
“…As expected (Niparko et al, 2003;Lin et al, 2006), the assessment of CROS benefit when speech is in front of the unilateral CI listener (Arora et al, 2013;Grewal et al, 2015) results in marginal benefit compared with those designed to measure head shadow effect (van Loon et al, 2014;Taal et al, 2016). Furthermore, these studies all used hearing aids (Arora et al, 2013;Grewal et al, 2015;Guevara et al, 2015;Weder et al, 2015;Taal et al, 2016) or lapel microphones (van Loon et al, 2014) hard-wired to a CI processor to deliver the contralateral microphone input. Although promising, such systems are not optimized for application in CIs, and variables such as directional microphones were not considered.…”
mentioning
confidence: 92%
See 2 more Smart Citations
“…As expected (Niparko et al, 2003;Lin et al, 2006), the assessment of CROS benefit when speech is in front of the unilateral CI listener (Arora et al, 2013;Grewal et al, 2015) results in marginal benefit compared with those designed to measure head shadow effect (van Loon et al, 2014;Taal et al, 2016). Furthermore, these studies all used hearing aids (Arora et al, 2013;Grewal et al, 2015;Guevara et al, 2015;Weder et al, 2015;Taal et al, 2016) or lapel microphones (van Loon et al, 2014) hard-wired to a CI processor to deliver the contralateral microphone input. Although promising, such systems are not optimized for application in CIs, and variables such as directional microphones were not considered.…”
mentioning
confidence: 92%
“…Rerouting of bilateral input for MLs is a promising alternative for patients who cannot benefit from binaural input (Arora et al, 2013;Weder et al, 2015;Taal et al, 2016). Early studies of CROS application in unilateral CI have demonstrated variable results (Arora et al, 2013;van Loon et al, 2014;Grewal et al, 2015;Guevara et al, 2015;Weder et al, 2015). Outcomes were reported in terms of hearing performance in noise.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, the net benefit of CROS devices in unilateral CI recipients has been mixed. Whereas some groups have reported that adding the CROS is not detrimental to speech understanding in noise when noise is presented to the CROS ear (Weder et al, 2015) or not significantly different (Wimmer et al, 2017), other work has shown a negative impact on speech understanding (Arora et al, 2013;Van Loon et al, 2014;Grewal et al, 2015;Taal et al, 2016). For speech understanding in quiet, some studies have shown no benefit of CROS (Taal et al, 2016), whereas other studies have demonstrated significant benefit for CROS with unilateral CI recipients (Arora et al, 2013;Grewal et al, 2015;Guevara et al, 2015).…”
mentioning
confidence: 99%
“…We would like to formally address the above article [Weder et al, 2015] in which it is mentioned in the Introduction section, paragraph 2, that '… a CROS device has never been studied as an aid to patients with a unilateral CI, a condition which has some similarities to single-sided deafness'.…”
mentioning
confidence: 99%